Study Antidiabetic Effect of Momordica Charantia (bitter gourd) seeds on Alloxan Induced Diabetic Rats: Auroba M.S.Ibrahem ;Nibras N.A. Al-Abassi - Ibrahem, Auroba M.S. (The Iraqi Journal of Veterinary Medicine, 2010)
The aim of the present study is to investigate the antidiabetic effect of the aqueous extract of Momordica charantia seeds in alloxan - induced diabetic rats. Forty male albino Wistar rats were used, divided randomly into four groups (10 each). Oral administration of the seed extract at a dose of 150 mg/kg B.W. for 30 days showed a significant decrease in fasting blood glucose. Our results were greatly lower after oral administration of aqueous extract of Momordica charantia seeds in alloxan- induced diabetic groups than glibenclamide treated group. Also Momordica charantia extract and glibenclamide administered rats showed progressive increase in body weight